2018
DOI: 10.17061/phrp2811806
|View full text |Cite
|
Sign up to set email alerts
|

Insights from linking routinely collected data across Australian health jurisdictions: a case study of end-of-life health service use

Abstract: Objectives: The jurisdictional nature of routinely collected health data in Australia has created challenges for linking data across state/territory and federal government boundaries. This has impeded understanding of the interplay between service use across hospital and community care. Our objective was to demonstrate the value-add of cross-jurisdictional data using a case study of health service use and the factors associated with healthcare use towards the end of life.Study type: Retrospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In the present study, we observed an overall higher use among men, but highly comparable trends among men and women, as confirmed by similar change points. Several studies have shown that older age is associated with lower use of acute healthcare services at the end of life 1 , 5 , 6 , 23 , 24 . This finding can be linked to a high proportion of institutionalized individuals who are regularly provided with basic assistance, potentially reducing the need to access hospital-based services, if not in close proximity to death, as suggested by the change point.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed an overall higher use among men, but highly comparable trends among men and women, as confirmed by similar change points. Several studies have shown that older age is associated with lower use of acute healthcare services at the end of life 1 , 5 , 6 , 23 , 24 . This finding can be linked to a high proportion of institutionalized individuals who are regularly provided with basic assistance, potentially reducing the need to access hospital-based services, if not in close proximity to death, as suggested by the change point.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, as well as internationally, there are barriers to hospital–community data sharing. Information sharing is of particular concern for both services when caring for patients who are frequently hospitalised at the EOL, and for whom rapid access to information is required to provide seamless and timely care (Langton et al., 2018). Poor interprofessional communication also limits GPs’ access to accurate information and their ability to provide optimal, coordinated care (McConnell, Butow, & Tattersall, 1999; O’Malley & Reschovsky, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in Australia linking health data across different jurisdictions found the same problems, that is, the processes remain costly and time-consuming. 61 However, the challenges are not insurmountable. In Scotland, an urgent-care data set linking NHS 24, ambulance service, primary care out of hours, ED, hospital and mortality data has been developed and contains complete patient pathway records from 2011.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…Internationally, the opportunities that the use of 'big data' can potentially bring to improving and transforming health care are recognised but critical issues remain around how data are collected, stored and used. 61,68 In particular, important factors around regulation, privacy and the need to reassure the public that their data are used legitimately and safely still need to be overcome. A policy analysis by Heitmueller et al 68 highlights how policy and legislation may help or hinder change in digital information gathering.…”
Section: Implications For Practicementioning
confidence: 99%